Effects of Cobalt and Chromium Loadings to The Catalytic Activities of Supported Metal Catalysts in Methane Oxidation - Mardwita Mardwita; Eka Sri Yusmartini; Nidya Wisudawati (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
A series of alumina supported cobalt and chromium catalysts with different metal loadings were prepared by impregnation method. Six types of alumina supported cobalt and chromium catalysts contained 5 wt%, 10 wt%, and 15 wt% loadings were produced and tested in methane oxidation. The catalysts were characterized by using x-ray diffraction (XRD) and carbon monoxide chemisorption (CO chemisorption). The XRD results do not confirmed any features of cobalt and chromium metal. The metal sizes for both catalysts were larger in high loading as shown by CO chemisorption results. Methane conversion results showed that the conversion increases with increasing the metal loading, however supported chromium catalysts were higher in activities compared to supported cobalt catalysts. Thermal stability tests on 15 wt% Co/Al and 15 wt% Cr/Al catalyst showed that supported chromium catalyst is more stable and maintain the particle size due to its strong interaction with support, while supported cobalt catalyst decrease in methane conversion due to deactivation of the catalyst. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).